(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2024)
Time has been the main architect at Viana Palace. Complexity is the result of a progressive adaptation to marquises of Viana’s vital needs and requirements. For over seven centuries, parts of a historical puzzle have been incorporated, modified, restructured and added, around twelve courtyards and a garden. In 1981 it was declared as Cultural Interest Heritage. The new restoration consisted in reversing structural pathologies detected in Patio de Recibo mezzanines, stables and on the roofs. Our project strategy solves those problems by combing traditional and contemporary constructive solutions, preserving the original atmosphere of the living house for the museum’s visitors. The aim after all was the same as in Tomaso di Lampedusa’s El Gatopardo “everything changes so that everything remains the same”. Doing what is not visible, that’s the idea in our Restoration of the Viana Palace. Key words: Restauration, Cordova, Viana Palace.